Pembuatan Fasilitas Pendukung Infrastruktur Belajar Mengajar di Pondok Pasantren Hidayatul Muslimin 1 di Jalan Parit Sembin Desa Parit Baru Kecamatan Sungai Raya Kabupaten Kubu Raya: The Production of Learning Support Infrastructure Facilities at Hidayatul Muslimin 1 Islamic Boarding School on Jalan Parit Sembin, Parit Baru Village, Sungai Raya District, Kubu Raya Regency - Rizal, Rizal; Sarpawi, Sarpawi; Asmadi, Asmadi; Sasongko, Hartanto Wahyu; Helyanto, Helyanto; Purnama, Ihkwan Arief; Setiawan, Randy; Anggraini, Irene; Reski, Indah Anjar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Islamic Boarding School Hidayatul Muslimin 1 is situated in West Kalimantan Province. This school features 19 classrooms constructed from basic wooden structures. The educational facilities available at this school, including tables, chairs, blackboards, and shoe racks, were insufficient to facilitate effective learning; some students even had to sit on the floor due to the lack of teaching and learning facilities. In addition, the classroom walls look dull because the paint has faded, so they display the original color of the wood that is the material of the classroom walls. This Community Service initiative aims to create learning facilities that will not only foster a comfortable learning environment for students but also enhance the practical skills of Civil Engineering students in woodworking applications. The Community Service team and Civil Engineering students who practiced woodworking at the Civil Engineering Department Workshop at Pontianak State Polytechnic executed the project to create these educational facilities. The learning facilities created for Hidayatul Muslimin 1 Islamic Boarding School in West Kalimantan include 20 tables, 40 chairs, two whiteboards, and four shoe racks. Additionally, with the support of Civil Engineering students, several teachers, and students from the Islamic boarding school, the Community Service team renovated and painted two classrooms.